Life satisfaction across sports disciplines and sports categories among Norwegian adolescents: comparisons to national data - Grasaas, Erik; Sandbakk, Øyvind (Frontiers in Psychology, 2025)
BackgroundAdolescence is a crucial time for engagement in physical activity (PA) as it linked to higher life satisfaction (LS) and future health. However, adolescents’ LS within the specific sport disciplines remains unexplored. The objective of this paper was to (1) describe LS, training behaviors and pain across 18 sports disciplines among Norwegian adolescents stratified by gender and (2) compare LS between the different sports disciplines and sports categories with nationwide data.MethodsCross-sectional data was derived from the Norwegian Youngdata Survey, collected with nationwide representation, aggregated from 2021 to 2023. A total of 26.171 adolescents aged 16 to 19 years were included, derived from 18 sports disciplines (e.g., football, handball, etc.) and grouped into categories (e.g., endurance sports, team sports, etc.). Comparisons to national data (N = 109.469) were conducted using summary data t-tests.ResultsAdolescents participating in cross-country (XC) skiing revealed the highest school satisfaction, highest PA levels, lowest pain and lowest painkiller usage across sport disciplines. Fifteen out of 18 sports disciplines revealed higher LS compared to national data, with substantial association in motorsport, XC skiing, football and handball (all, p < 0.002). All sport categories revealed higher LS compared to national data (all, p < 0.01), whereas the strongest associations were unveiled among girls (all, p < 0.002).ConclusionParticipation in sports, regardless of category, is associated with increased LS of Norwegian adolescents, with strongest associations unveiled among girls. With this research, we add further insights into adolescents’ life satisfaction, training, pain and painkiller use, providing novel sport-specific knowledge of both healthy and risk-behavior.